2014
DOI: 10.1103/physrevd.90.124028
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic symmetries and subleading soft graviton theorem

Abstract: Motivated by the equivalence between soft graviton theorem and Ward identities for the supertranslation symmetries belonging to the BMS group, we propose a new extension (different from the so-called extended BMS) of the BMS group which is a semi-direct product of supertranslations and Diff(S^2). We propose a definition for the canonical generators associated to the smooth diffeomorphisms and show that the resulting Ward identities are equivalent to the subleading soft graviton theorem of Cachazo and Strominge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
527
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(545 citation statements)
references
References 52 publications
(189 reference statements)
18
527
0
Order By: Relevance
“…In [60], the same set of authors concluded that the Virasoro central terms were 2 This section was worked out in collaboration with Anandita De. 3 Here it is of interest to mention that the BMS4 group has also been recently extended differently to include all smooth vector fields on S 2 instead of extending the global conformal symmetries to Virasoro symmetries [57,58]. This generalisation of the BMS group is thus the semi-direct product of the supertranslations with Diff(S 2 ), the group of smooth conformal deformations of the sphere at null infinity.…”
Section: Symmetries Of Bmsmentioning
confidence: 99%
“…In [60], the same set of authors concluded that the Virasoro central terms were 2 This section was worked out in collaboration with Anandita De. 3 Here it is of interest to mention that the BMS4 group has also been recently extended differently to include all smooth vector fields on S 2 instead of extending the global conformal symmetries to Virasoro symmetries [57,58]. This generalisation of the BMS group is thus the semi-direct product of the supertranslations with Diff(S 2 ), the group of smooth conformal deformations of the sphere at null infinity.…”
Section: Symmetries Of Bmsmentioning
confidence: 99%
“…Since the seminal work by Strominger [1], there has been a flurry of activity towards understanding the role of a class of symmetries known as "asymptotic symmetries" in gauge theories and gravity [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. For theories containing massless particles of spin 1 ≤ s ≤ 2, asymptotic symmetries are obtained by considering gauge transformations which do not fall off at infinity.…”
Section: Introductionmentioning
confidence: 99%
“…The content of Noether's theorem for incompressible fluids is that the convected momentum is always a constant independent of time. 5 As a result, we get a conserved quantity,…”
Section: Jhep10(2017)049mentioning
confidence: 99%
“…For certain choices of boundary conditions, the Lorentz subgroup is enlarged as well, to an infinite dimensional group of superrotations. Depending on the choice of boundary conditions, the superrotations comprise either the infinitesimal conformal transformations of the two-sphere [3,4] or else the smooth diffeomorphisms of the two-sphere, Diff(S 2 ) [5,6].…”
Section: Introductionmentioning
confidence: 99%